Concave Pattern of a Maximal Expiratory Flow-Volume Curve: A Sign of Airflow Limitation in Adult Bronchial Asthma - Ohwada, Akihiko; Takahashi, Kazuhisa (Pulmonary Medicine, 2012)
Background. In patients with bronchial asthma, spirometry could identify the airflow limitation of small airways by evaluating the concave shape of the maximal expiratory flow-volume (MEFV) curve. As the concave shape of the MEFV curve is not well documented, we reevaluated the importance of this curve in adult asthmatic patients. Methods. We evaluated spirometric parameters, the MEFV curve, and its concave shape (scoop between the peak and endpoint of expiration) in 27 nonsmoking asthmatic patients with physician-confirmed wheeze and positive bronchial reversibility after a short-acting β2-agonist inhalation. We also calculated angle β and shape factors (SF25% and SF50%) to quantitate the curvilinearity of the MEFV curve. Results. The MEFV curve was concave in all patients. Along with improvements in standard spirometric parameters, curvilinear parameters, angle β, SF25%, and SF50% were significantly improved after bronchodilator inhalation. There were significant correlations between improvements in angle β, and FEF50%, and FEF25-75%, and between improvements in SF25%, and SF50%, and FEF75%. Conclusions. The bronchodilator greatly affected the concave shape of the MEFV curve, correlating with spirometric parameters of small airway obstructions (FEF50%, FEF75%, and FEF25-75%). Thus, the concave shape of the MEFV curve is an important indicator of airflow limitation in adult asthmatic patients.